2020
DOI: 10.1021/acsaem.0c01121
|View full text |Cite
|
Sign up to set email alerts
|

Multicomponent Spinel Metal Oxide Nanocomposites as High-Performance Bifunctional Catalysts in Zn–Air Batteries

Abstract: Although multicomponent transition-metal oxides have been widely studied as electrocatalysts in both the oxygen reduction reaction (ORR) and the oxygen evolution reaction (OER), precise control of catalytic activities by varying the composition of these metal elements is not an easy task. In this work, we introduce a generic and scalable synthetic method by dealloying a series of Al-rich precursor alloys to produce Mn 3 O 4 -based and FeCo-based spinel oxide nanocomposites. It is found that these Mn 3 O 4 -bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 47 publications
0
17
0
Order By: Relevance
“…In particular, Mn oxides are of interest in electrochemistry, [1,2] (photo) catalysis, [3][4][5][6][7] and for the development of batteries and magnetic devices. [8][9][10] The phase diagram of the Mn-O system shows several oxides with well-defined stoichiometry, ranging from MnO 2 to MnO, which are stable in definite intervals of temperature and oxygen partial pressure. [11,12] This variety of structures and redox states is essential to explain the interest of these systems in multiple energy applications.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, Mn oxides are of interest in electrochemistry, [1,2] (photo) catalysis, [3][4][5][6][7] and for the development of batteries and magnetic devices. [8][9][10] The phase diagram of the Mn-O system shows several oxides with well-defined stoichiometry, ranging from MnO 2 to MnO, which are stable in definite intervals of temperature and oxygen partial pressure. [11,12] This variety of structures and redox states is essential to explain the interest of these systems in multiple energy applications.…”
Section: Introductionmentioning
confidence: 99%
“…The HR-TEM image indicates that Mn3O4 nanosheets exist as the elongated sphere-like nanoparticles with a size of 50 nm and a thickness estimated to be 10-20 nm (Figure 1b). Based on the polarization studies, the AlFeCoNiMn modified electrode showed a higher open-circuit potential (1.44 V) compared to the commercial Pt/C + IrO2 electrode (1.41 V) (Figure 1c) [41]. Copyright 2020 by American Chemical Society [41].…”
Section: Nanoscale-based Electrode Catalysts For Metal-air Batterymentioning
confidence: 99%
“…Based on the polarization studies, the AlFeCoNiMn modified electrode showed a higher open-circuit potential (1.44 V) compared to the commercial Pt/C + IrO2 electrode (1.41 V) (Figure 1c) [41]. Copyright 2020 by American Chemical Society [41].…”
Section: Nanoscale-based Electrode Catalysts For Metal-air Batterymentioning
confidence: 99%
See 2 more Smart Citations